AI Adoption in Higher Education Institution: An Integrated TAM and TOE Model - Djoko Setyo Widodo; Dwi Rachmawati; Hadi Wijaya; Alfi Maghfuriyah; Udriya Udriya (Dinasti Publisher, 2025)
Artificial Intelligence (AI) impacts various daily activities and features, including higher education. Educators and academics now see AI in education to be essential. The benefits of higher education and how universities adjust to shifting student and faculty attitudes on learning are topics of growing discussion. This study aims to explore how policymakers and educators may apply AI and modify it for the learning domain. The integrated technology acceptance model (TAM)-TOE model was implemented in a conceptual model that was released. It was tested with survey data obtained from 200 respondents who participated in an online survey, and a structural equation model (SEM-PLS) was utilized to assess the suggested hypotheses. The results show that organizational readiness, organizational compatibility, and partner support on perceived ease of use had been correlated with any significant relationship evaluated in the setting of higher education. It is anticipated that the approach will help authorities facilitate the use of AI in higher education. Furthermore, as AI is still in its infancy, more academic study is required before it can be used to the sector of education.